INTERDISCIPLINARY APPROACH IN FUTURE SOFTWARE ENGINEERS PROFESSIONAL TRAINING - V. Kruglyk; V. Osadchyi (Borys Grinchenko Kyiv Metropolitan University, 2017)
The authors examine the problem of future software engineers training in the context of the multidisciplinary approach. The description of the specific activity of future professional software engineers according to the three types of occupations as to the object of labour ("man-technique", "man-sign system", "man-man") is presented. The authors emphasize that the interaction of software engineering and mathematics in teaching future programmers is necessary to address training competitive specialists in the modern labour market and to adapt to modern requirements of IT business professionals. Today the issue becomes relevant, the efficient processing of "big data" analysis and visual presentation are used in today's economy for collecting valuable information to meet the needs of company's analytics within their industry. According to domestic and foreign appropriate experience in future, software engineers training sessions have to include two parts: mathematics and software engineering. The paper shows that the future software engineer should be able to apply knowledge of economics, because any software has to be in demand in the consumer market, so the student must be acquainted with the economy of software engineering. The use of the multidisciplinary approach in future software engineers training is considered as a part of the development of their professional competence through the implementation of communication of humanitarian, socio-economic, mathematical disciplines and natural-science training. It is determined that each of these disciplines provides knowledge in the form of objects, phenomena, principles, approaches used in the development of software engineers.